SELF REGULATED LEARNING OF MATHEMATICS EDUCATION STUDENT OF IAIN CURUP - Fevi Rahmadeni (Jurnal Equation: Teori dan Penelitian Pendidikan Matematika, 2021)
This research is motivated by the importance of student learning independence in supporting the successful implementation of online learning. The purpose of this study was to determine the level of learning independence of students of the Mathematics Tadris Study Program of IAIN Curup. Learning independence is a person's ability to regulate himself in learning. Online learning that has been going on for about a year has led students to be able to take part in learning independently from home so that learning independence is needed so that students can participate in learning to the fullest. Learning independence is categorized into 5 levels, namely very high, high, medium, low, and very low. This type of research is qualitative. The analysis was carried out using the help of Microsoft excel. The results obtained indicate that as many as 10.9% of students have a low level of self regulated learning and 4.35% of students have a very high level of learning independence. Therefore, in the future, efforts are needed to increase students' independent learning attitudes.